N-(4-Bromophenyl)-2-[(1-cyclohexylmethyl-1H-1,2,4-triazol-3-yl)sulfanyl]acetamide - Wang, Yue-Ping (International Union of Crystallography, 2012)
The title compound, C(17)H(21)BrN(4)OS, was synthesized as a potential reverse transcriptase (RT) inhibitor of the human immunodeficiency virus type 1 (HIV-1). In the molecule, there is an N—H⋯S hydrogen bond making a five-membered ring. In the crystal, molecules are connected into centrosymmetric dimers via pairs of N—H⋯N and weak C—H⋯N hydrogen bonds. The crystal structure also features C—H⋯O interactions.